Transmission Matrix Based Image Super-Resolution Reconstruction Through Scattering Media - Shenghang Zhou; Xiubao Sui; Yingzi Hua; Qian Chen; Guohua Gu; Hongyang Bai (IEEE Photonics Journal, 2020)
Measuring optical transmission matrix has enabled image detection through scattering media, however its retrieved resolution is severely limited by the number of measurements. In this paper, we introduce super resolution reconstruction into transmission matrix based imaging scheme, to some extent bypassed this limitation. We demonstrate all detailed information of high-resolution subpixel shifting target are preserved in its corresponding speckle signals. And through phase conjugate reconstruction one can get target's low-resolution projection images with accuracy. The final high-resolution image is achieved by subpixel registration and bilinear interpolation operations. The feasibility of the proposed method is theoretically analyzed and proved by laboratory experiments.